The impact of assets structure and the components of cash conversion cycle on the Egyptian SMEs financial failure predictability - Hassan Mounir El-Sady; Hatem Ahmed; Hosny Hamdy (The Journal of Entrepreneurial Finance (JEF), 2022)
This study investigates determinants of Egyptian SMEs financial failure predictability based on a sample of 32 failure SMEs and 28 non-failure SMEs for the period 2013 and 2019. The determinants of SMEs financial failure are categorized into four groups; Working Capital, Asset Structure, Liquidity, and Leverage. The factor and logistic regression analysis are employed to identify the most significant independent variables that classify between failure and none-failure Egyptian's SMEs and determine the driver of SMEs financial failure. Our findings significantly show that failing SMEs suffer from long cash conversion cycles resulting from long inventory holding period, average collection period, and short average payment period, in addition to lower liquidity, excessive use of debt to assets, and lower fixed assets percentage, in contrast to non-failure Egyptian's SMEs.
Keywords: 650; SMEs; Financial Failure; Working Capital; Leverage; Liquidity; Asset Structure; Factor Analysis; and Logistic Regression